Tempeh's Probiotic Bacteria Content can Boost Its Value as a Functional Food in the COVID-19 Era - Dewi Peti Virgianti; Rochmanah Suhartati (Health Notions, 2023)
The The COVID-19 era is far from over, especially with the emergence of new virus variants. Efforts to develop vaccines and treatments have been made, but various prevention strategies must still be developed in order to combat this pandemic. Probiotics are cultures of one type or a mixture of live bacteria that help to maintain the balance of the gut microbiota, which is important for the host's health. Various studies have presented evidence that probiotics have the ability to boost human immunity. Tempe is a fermented Indonesian food, some contain probiotics. Probiotic bacteria found in tempe include Lactobacillus fermentum, Lactobacillus plantarum, Lactobacillus paracasei, Lactobacillus delbrueckii, Lactobacillus agilis, Lactobacillus mucosae, Lactobacillus paralimentarius, Lactobacillus zeae, Lactococcus sp, Weisella confusa, Weissella paramesenteroides, Enterococcus faecalis, Enterococcus faecium, Pediococcus pentosaceus. In this study, we present the potential of probiotic bacteria origin tempeh that have been shown to improve host health, particularly in terms of increasing immunity, preventing respiratory infections, and lowering risk factors for comorbidities. The data presented is expected to provide an overview of the potential consumption of tempeh as a functional food, particularly in this era of the COVID-19, so that awareness of the benefits of this beneficial food grows. Keywords: fermentation; health; bacteria